Saisir le « non-lieu » : usages utopiques de l’île dans la littérature européenne d’après-guerre - Ioana Andreescu (Itinéraires, 2015)
Considering island novels as a fictional laboratory for society, this paper seeks to interrelate post-war utopian literature and European history. Our case studies are Lord of the Flies (1954) by William Golding and Island (1962) by Aldous Huxley. From different perspectives, both literary utopias and the history of mentalities appear to apprehend social realities and rethink politics. After World War II, the island narrative reveals a critique of totalitarian ideologies, and an interrogation of the violence of that past that equally implies a mental exercise of envisioning future.